Development and validation of a new multiplex Y‐STR panel designed to increase the power of discrimination. Issue 18 (4th August 2022) - Zhou, Yongsong; Cui, Wei; Wu, Buling; Zhu, Bofeng
Abstract: In an attempt to increase the discrimination capacity (DC) and reduce the adventitious match probability, a 6‐dye multiplex Y‐chromosomal short tandem repeat (Y‐STR) panel named Y34plex was constructed that combined 25 Y‐chromosomal markers (DYS456, DYS627, DYS390, DYS570, DYS635, DYS385a/b, DYS448, DYS437, DYS533, DYS449, DYS481, DYS392, DYS391, DYS389I, DYS460, YGATAH4, DYS438, DYS389II, DYS19, DYS458, DYF387S1a/b, DYS439, DYS393, DYS576, and DYS518) in widely used commercial kits, with nine highly polymorphic Y‐STR loci (DYS557, DYS527a/b, DYS593, DYS444, DYS596, DYS643, DYS447, DYS549, and DYS645). The Y34plex is a promising type system to distinguish both unrelated and related male individuals due to the incorporation of rapidly mutated Y‐STR loci. A validation study of the Y34plex was performed and followed the guidelines of the Scientific Working Group on DNA analysis methods. Results show that full Y‐STR profiles were obtained from male/female DNA mixtures with 125 pg of male DNA in the presence of 50 ng of female DNA. The ability to tolerate polymerase chain reaction inhibitors commonly contained in forensic casework samples demonstrated the applicability and robustness of the Y34plex. Compared with the Yfiler Plus kit, the novel panel showed an increased power of discrimination in Chinese Wuxi Han population ( n = 434). The overall haplotype diversity of the Y34plex was 0.999606, whereas DC value was 0.956221, which is suitable for use on forensic paternal investigation.